DETOKSIFIKASI HIDROLISAT ASAM DARI UBI KAYU UNTUK PRODUKSI BIOETANOL - Yuana Susmiati (AGROINTEK, 2011)
The production of bioetanol by using acid hydrolisis method resulted the formation of compounds which can destructed the fermentation process, such as HMF or furfural, thus it needs detoxification process to erase or decrease it. Detoxification process is done by adding alkali in to hidrolisat before it is used as fermentation substrat. Alkali compound which is usually used are Ca(OH)2 or NH4OH. This research is conducted to compare ethanol rendement resulted from the detoxification process, and also to decide the most optimal detoxification that can be done to produce the best etanol rendement. The study is done by using distinct treatmentof catalist, that are Ca(OH)2 dan NH4OH as well as the stirring/mixing time, which are control, 15, 30 and 45 minutes during detoxification process. Based on the result of the study, it can be concluded that etanol rendement resulted from hydrolisat which is detoxificated by using catalyst NH4OH is higher than the one which use catalyst Ca(OH)2. Acid hydrolisat detoxification method from cassava in order to produce an optimal bioetanol is by using catalist NH4OH with free stirring time(less than 15 minutes)